2021
DOI: 10.1155/2021/1207646
|View full text |Cite
|
Sign up to set email alerts
|

Ricci Curvature for Warped Product Submanifolds of Sasakian Space Forms and Its Applications to Differential Equations

Abstract: In the present paper, we establish a Chen–Ricci inequality for a C-totally real warped product submanifold M n of Sasakian space forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…e geometric structure and topological properties of submanifolds in different spaces have been studied on a large scale during the past few years [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Many results showed that there is a closed relationship between stable currents which are nonexistent and the vanished homology groups of submanifolds in a different class of the ambient manifold obtained by imposing conditions on the second fundamental form (1).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…e geometric structure and topological properties of submanifolds in different spaces have been studied on a large scale during the past few years [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Many results showed that there is a closed relationship between stable currents which are nonexistent and the vanished homology groups of submanifolds in a different class of the ambient manifold obtained by imposing conditions on the second fundamental form (1).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…More recently, several results have been derived on topological and differentiable structures of submanifolds when imposing certain conditions on the second fundamental form, Ricci curvatures, and sectional curvatures in a series of articles [4,10,11,[18][19][20][21][22][23] by different geometers. For the warped product structure, we refer to [20,[24][25][26][27][28][29][30].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Furthermore, Al-Dayael and Khan [19] proved that, under certain conditions, the base of contact CR-warped product submanifolds N T × f N ⊥ is isometric to a sphere. Recently, Mofarreh et al [20] used Obata's differential equation on warped product submanifolds of Sasakian space form and established some characterization.…”
Section: Introductionmentioning
confidence: 99%